Guerriers déclassés et captifs combattants. Des masculinités indiennes confrontées à la guerre du Chaco (1932-1935) - Luc Capdevila (Centre de Recherches sur les Mondes Américains, 2013)
This study questions the impact of colonization on the construction of gender in Native American societies through their figures of manhood in the Chaco Boreal 20th century, especially during the war between Paraguay and Bolivia. The analysis is based in particular on individual trajectories. Thereby, we observe how the Indian male hierarchies, built on a bipolar system (warrior/captive), were absorbed and dissolved in the Western hierarchies through the military experience.